Rethinking Islamic Education in the Digital Age: Toward a Philosophical Framework for Cyber-Based Distance Learning - Putra, Andri Azis; Yunianika, Ika Tri (Alhamra Jurnal Studi Islam, 2025)
The shift of education into a digital and distance-based format is not merely a technological transformation, but a profound change in the very nature of learning itself. However, within this epistemic transition, Islamic education has yet to establish a robust philosophical foundation that aligns its core values with the demands and potentials of the digital space. This study aims to construct a philosophical framework for cyber-based Islamic distance education. Employing a hermeneutic-philosophical approach, it integrates textual analysis of Islamic sources with contemporary thought on technology and education. As a library-based study, the data primarily consists of textual analysis and observation of several e-learning platforms used by Islamic cyber universities. Verification is conducted through source and method triangulation. The findings of this research offer a reconceptualization of the learner as a Cyber-student—a seeker of knowledge who acts with a clear purpose, epistemic inclination, and dialogical participation. Within this framework, Islamic distance education can be understood as a space for the cultivation of ethics, purification of the self, and the attainment of wisdom. The study yields design principles that integrate spiritual ethics with approaches inspired by a tawhidic vision, challenging algorithmic reductionism and affirming the potential of the digital space as a sacred epistemological domain.